Leveraging preexisting exotic Piper aduncum L. vegetation as a nurse plant to restore successional grasslands in Mindanao, the Philippines - Jawani, Rovana M.; Tulod, Adrian M.; Forest restoration (2024)
Restoration planting with nurse plants is an effective strategy for forest restoration in harsh habitats. In cases where native nurse plants are absent, colonizing exotic vegetation in degraded successional grasslands may be used as nurse species in restoration projects, provided they do not outcompete or suppress the target native plants beneath their canopy. In this study, a threeyear restoration planting trial was conducted within a successional grassland using different manipulative planting techniques to test the potential of the invasive exotic Piper aduncum L. to serve as a nurse plant for indigenous tree species. The treatments included understory planting, edge planting, and open grassland. Three shade-tolerant species from the Dipterocarpaceae family were used for restoration – namely Rubroshorea polysperma (Blanco) P.S.Ashton & J.Heck., Rubroshorea ovata (Dyer ex Brandis) P.S.Ashton & J.Heck., and Parashorea malaanonan (Blanco) Merr. Seven seedlings per species were planted in each treatment, replicated across six locations, totaling 378 seedlings. The treatments varied significantly in terms of canopy openness and light conditions. No significant differences in growth performance were observed among the dipterocarp species, regardless of treatment. However, seedlings – irrespective of species – grew significantly better and had higher survival rates at the canopy edge sites, where moderate canopy openness and light conditions were present, compared to understory and open sites. Seedling growth performance, measured in relative height and diameter growth, and survival rates were positively correlated with moderate light levels, particularly between 1.1 to 1.4 mol m⁻² d⁻¹, found at the edge sites. This study demonstrates that preexisting invasive exotic P. aduncum can be managed to act as a nurse plant to facilitate the establishment of canopy species in harsh and degraded environments such as successional grasslands.
Keywords: Indigenous plants; Conservation and restoration